Why Costumers Have The Intention to Repurchase at Coffee Shops in Bogor? Explaining The Role of Social Media Marketing, Dining Atmosphere, and Relationship Marketing - Alim Setiawan; Almas, Caesavela; Indrawan, Dikky (Jurnal Manajemen dan Agribisnis, 2021)
This study aims to determine the impact of relationship marketing, social media marketing, and dining atmosphere on customer trust and repurchase intention. This study was conducted by surveying 407 customers who frequently visited Ngopi Doeloe, Popolo Coffee, Ranin Coffee House, Starbucks Coffee, Jco Donuts & Coffee, and The Coffee Bean & Tea Leaf, and Structural Equation Model (SEM) was used to test the research hypotheses. The findings supported the hypotheses that relationship marketing and social media marketing positively affected repurchase intention and customer trust. Relationship marketing had the greatest influence on customer trust in local coffee shops. In contrast, the dining atmosphere did not affect repurchase intention.Keywords: customer trust, dining atmosphere, relationship marketing, repurchase intention,social media marketing